2013
DOI: 10.1097/sle.0b013e318277df6a
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Interval Appendectomy Versus Open Interval Appendectomy

Abstract: This was a prospective randomized controlled study designed to compare laparoscopic and open interval appendectomy and involved 100 patients of appendicular phlegmon. After initial conservative management, patients were divided into 2 groups of 50 each and interval appendectomy was performed by laparoscopy in one of the groups and by open method in the other. Mean operative time in open surgery was 33.9 minutes and that in laparoscopic surgery was 57.64 minutes (P < 0.05). Concomitant pathology was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 18 publications
4
22
0
11
Order By: Relevance
“…de la apendicectomía abierta en comparación con la laparoscópica (15,1 % Vs. 3,7 %,respectivamente), además de tener una tendencia a mayor estancia hospitalaria y reintervención. Los pacientes de apendicectomía abierta tuvieron mayor infección en la incisión del sitio operatorio (8,7 % Vs. 2,8 %;p=0,01).…”
Section: Resultados Se Incluyeron 600 Pacientes: 389 Apendicectomíasunclassified
See 1 more Smart Citation
“…de la apendicectomía abierta en comparación con la laparoscópica (15,1 % Vs. 3,7 %,respectivamente), además de tener una tendencia a mayor estancia hospitalaria y reintervención. Los pacientes de apendicectomía abierta tuvieron mayor infección en la incisión del sitio operatorio (8,7 % Vs. 2,8 %;p=0,01).…”
Section: Resultados Se Incluyeron 600 Pacientes: 389 Apendicectomíasunclassified
“…No se presentaron diferencias estadísticamente significativas con respecto a la estancia hospitalaria, pero hubo una tendencia a ser mayor con la técnica abierta. No se exploraron variables como el dolor posoperatorio, el tiempo de tolerancia a la vía oral, el tiempo de regreso a las actividades cotidianas y el resultado cosmético de la intervención; sin embargo, en la literatura se menciona también la superioridad de la técnica laparoscópica en todos estos aspectos 7,10,13,15 . Con respecto 16 .…”
Section: Discussionunclassified
“…Unlike in conventional surgery for SSI, we were able to completely remove the necrotic tissue and infected suture in visualization under the endoscopy procedure. For small sinuses that could not be reached by endoscopy, the necrosis was removed by biopsy clip (16,17). The results demonstrated that endoscopy decreased the wound healing time, the rate of skin transplantation, the blood loss and the length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no statistical difference between both groups. In many studies, LA has been attributed with a relatively low incidence of complications compared with OA 20, 21 .…”
Section: Discussionmentioning
confidence: 99%